Inquisition and Empire: The Holy Office of Goa between Padroado and Propaganda Fide (1666-1681) - Rodrigues Lourenço, Miguel (Anuario de Historia de América Latina, 2020)
During the dispute between Portugal and the Holy See over the rights of Patronage (Padroado real) in Asia, the Inquisition played a secondary role in the legal allegations of the Crown. In the local context of the controversies with the apostolic vicars sent by the Congregation de Propaganda Fide, priests and missionaries of the Portuguese Padroado saw the Holy Office as an instrument to defend the rights of the Crown, arresting and excommunicating on behalf of the tribunal. Imperial agents in the Estado da Índia envisioned the Inquisition as an instrument for claiming jurisdictional rights over territory, while they also faced conflicts with the inquisitors.